Market Orientation, Innovativeness and Performance in E-Learning Programme of Sri Lankan Universities - Sathana, V.; Samarakoon, S.M.A.K. (University of Kelaniya, 2015)
The purpose of the study is to explore the market orientation, innovativeness and performance of the government Universities in Sri Lanka. Sri Lankan Universities were the unit of analysis. Data for this study were collected from the faculty heads or coordinators of Higher education programmmes in government Universities in Sri Lanka. Convenient sampling method was adopted, structured questionnaires were issued directly and sent through the mail to collect data and one hundred and fourteen respondents were gathered in this study. The MARKOR was used to measure the Market Orientation. Correlation and regression analysis were used in order to identify the association among market Orientation, innovativeness and performance. Three market orientation measures included intelligence generation; intelligence dissemination and responsiveness to intelligence were used to investigate their relationships with Innovativeness and performance. All three measures were found to be statistically significant and positively related to the Innovativeness and performance of the course programmes Universities in Sri Lanka. Based on the studies, the Universities were suggested to follow proper market oriented strategy in higher education system, it will lead to optimum performance achievement.
Keywords: Innovativeness; Market Orientation; Performance; University